Implementation of Team Teaching Learning through the Collaboration of Zoom Cloud Meeting and Live Broadcasting Technology during the Covid-19 Pandemic - Edy Prihantoro; Dwi Asih Haryanti; Noviawan Rasyid Ohorella (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Online learning is the choice of higher education managers during the Covid 19 pandemic. Higher education managers must be able to manage online learning. One of the universities that innovates learning systems by combining zoom cloud meeting technology and live broadcasting at UGTV is Gunadarma University. Through these two platforms, lecture materials are distributed to students. Learning materials are prepared by Team Teaching,  a learning strategy in which learning activities are carried out by one or more lecturers according to their respective  roles and responsibilities. The shortcomings of online lectures using zoom are related to network constraints,  the availability of  internet quotas,   and display quality. By combining zoom cloud meeting and broadcasting, network constraints, quotas, participant capacity and on air look better and more attractive to students. This study aims to determine how the implementation of learning through the collaboration of zoom and broadcasting technology. The method used is descriptive qualitative method. The results showed that through online learning distributed through zoom and UGTV, with learning materials prepared by team teaching it could facilitate student learning, both using zoom and UGTV.